Nonsmall-cell lung cancer treatment: current status of drug repurposing and nanoparticle-based drug delivery systems - Inci, Tugba Gul; Acar, Serap; Turgut-Balik, Dilek (Tubitak Scientific & Technological Research Council Turkey, 2024)
Drug repurposing is the strategy of drug utilization for a treatment option other than the intended indications. This strategy has witnessed increased adoption over the past decades, especially within cancer nanomedicine. Cancer nanomedicine has been facilitated through nanoparticle-based (NP -based) delivery systems which can combat nonsmall-cell lung cancer (NSCLC) via recent advances in nanotechnology and apply its benefits to existing drugs. The repurposing of drugs, coupled with NP -based drug delivery systems, presents a promising avenue for achieving effective therapeutic solutions with accelerated outcomes. This review aims to present an overview of NSCLC treatments, with a specific focus on drug repurposing. It seeks to elucidate the latest advances in clinical studies and the utilization of NP -based drug delivery systems tailored for NSCLC treatment. First, the molecular mechanisms of Food and Drug Administration (FDA) -approved drugs for NSCLC, including ROS1 tyrosine kinase inhibitors (TKI) like repotrectinib, approved in November 2023, are detailed. Further, in vitro studies employing a combination strategy of drug repurposing and NP -based drug delivery systems as a treatment approach against NSCLC are listed. It includes the latest study on nanoparticle-based drug delivery systems loaded with repurposed drugs.
Keywords: Drug repurposing; nonsmall-cell lung cancer; NSCLC; nanoparticle-based drug delivery systems; TYROSINE KINASE INHIBITORS; FDA APPROVAL; 1ST-LINE TREATMENT; PLUS CARBOPLATIN; NAB-PACLITAXEL; CRIZOTINIB; ITRACONAZOLE; CHEMOTHERAPY; DISULFIRAM; Life Sciences & Biomedicine - Other Topics